Mechanism of Action and Some Properties of a Tissue Activator of Plasminogen - McCall, Dolly Cannamela; Kline, D. L (Thrombosis and Haemostasis, 1965)
1. Improvements in preparations of tissue activator and plasminogen and termination of activation by epsilon aminocaproic acid have permitted the use of a quantitative caseinolytic assay for the measurement of the plasmin formed. The following data indicate that the activation of plasminogen by tissue activator is catalytic :a) Biphasic curve obtained when velocity was plotted against plasminogen concentration.b) First order kinetics.c) Dependence of the turnover number on tissue activator concentration.2. The temperature and pH stability of tissue activator were similar to those reported for urokinase. Since both of these enzymes have now been shown to activate plasminogen by a catalytic mechanism, these data support the suggestion that urokinase may be an excretory form of tissue activator which has been released into the circulation.